Transient decrease in circulating dendritic cell precursors after acute stroke: Potential recruitment into the brain - Yilmaz, Atilla; Fuchs, Tanja; Dietel, Barbara; Altendorf, Regina; Cicha, Iwona; Stumpf, Christian; Schellinger, Peter D.; Blümcke, Ingmar; Schwab, Stefan; Daniel, Werner; Garlichs, Christoph; Kollmar, Rainer (Clinical Science, 2010)
The role of DCs (dendritic cells) as potent mediators of inflammation has not been sufficiently investigated in stroke. Therefore, in the present study, circulating mDCPs (myeloid DC precursors), pDCPs (plasmacytoid DCPs) and tDCPs (total DCPs) were analysed by flow cytometry in (i) healthy controls (n = 29), (ii) patients with ACI-S (asymptomatic cerebral infarction stenosis; n = 46), (iii) patients with TIA (transient ischaemic attack; n = 39), (iv) patients with AIS (acute ischaemic stroke; n = 73), and (v) patients with AHS (acute haemorrhagic stroke; n = 31). The NIHSS (National Institutes of Health Stroke Scale) and infarction size on a CT (computer tomography) scan were evaluated after stroke. In a patient subgroup, post-mortem immunohistochemical brain analyses were performed to detect mDCs (CD209), pDCs (CD123), T-cells (CD3) and HLA-DR. In AIS and AHS, the numbers of circulating mDCPs (P < 0.005), pDCPs (P < 0.005) and tDCPs (P < 0.001) were significantly reduced. A significant inverse correlation was found between the NIHSS and circulating DCPs (P < 0.02), as well as between hsCRP (high-sensitivity C-reactive protein) and circulating DCPs (P < 0.001). Patients with large stroke sizes on a CT scan had significantly lower numbers of mDCPs (P = 0.007), pDCPs (P = 0.05) and tDCPs (P = 0.01) than those with smaller stroke sizes. Follow-up analysis showed a significant recovery of circulating DCPs in the first few days after stroke. In the infarcted brain, a dense infiltration of mDCs co-localized with T-cells, single pDCs and high HLA-DR expression were observed. In conclusion, acute stroke leads to a decrease in circulating DCPs. Potentially, circulating DCPs are recruited from the blood into the infarcted brain and probably trigger cerebral immune reactions there. © The Authors Journal compilation © 2010 Biochemical Society.
CRIS-Team Scopus Importer:2024-12-04
Keywords: Dendritic cell; Inflammation; Ischaemic brain injury; Leucocyte infiltration; Stroke; T-cell activation